MODERASI BERAGAMA SEBAGAI BENTENG TOLERANSI DI INDONESIA - Yahya, Yulia Putra (JOURNAL J-MPI : JURNAL MANAJEMEN PENDIDIKAN, PENELITIAN DAN KAJIAN KEISLAMAN, 2024)
This article tries to review religious moderation which can act as a bulwark of tolerance.In this case it can be said that Indonesia is a country which does not only have one religion but has several diverse religion,therefore religious moderation in really needed as a bulwark of tolerance and can making people’s lives comfortable and harmonious.In thi research ,in terms of collecting information,the author used the library study method.the data sources in this paper come from the web,journals and books and even other literature that is possible and related.The objectives to be achieved in this paper namely to explore the concept of religious moderation as a bulwark of tolerance,explore the importance of religious moderation as a bulwark of tolerance and also the obstacles or challenges that may be experienced in religious moderation as a bulwark of tolerance